BEING A PHYSICAL EDUCATION TEACHER OF UNIPLAC - CONSTRUCTING IDENTITIES (Fiep Bulletin - online, 2014)
This work had as objective to discuss the construction of a professional identity to Physical Education teacher (UNIPLAC), in order to understand how works the construction process of that professional identity. It is an empirical research from a participant observation. Some researchers used in this study are Tardif (2002); Pimenta & Anastasiou (2005). In this sense, the professional identity of the Physical Education teacher of UNIPLAC is constructed through teaching activity, permanent formation and consolidation of the knowledge acquired throughout academic years. In relation to the observations made, it was evident that teaching practice and knowledge are important and contribute in the construction of this identity process.
Keywords: Professional identity; Physical Education Teacher; Teaching practice